2021
DOI: 10.2519/jospt.2021.10533
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Neurodynamic Techniques for Treating Carpal Tunnel Syndrome: A Systematic Review With Meta-analysis

Abstract: Objectives We aimed (1) to estimate the short-term effect (postintervention period) of neurodynamic techniques on pain, symptom severity, functional status, electrophysiological status, grip strength, and pinch strength in people with carpal tunnel syndrome (CTS); and (2) to estimate the effect of neurodynamic techniques compared to other physical therapy modalities and surgical interventions. Design Intervention systematic review with meta-analysis. Literature Search We searched the MEDLINE, Cochrane Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…However, study by Wolny and Linek (n = 180) found clinically important benefit for the neurodynamic group in the BCTQ symptom severity score (mean difference 1.22 points; 95% 1.1 to 1.4 points), BCTQ functional scale (mean difference 0.9; 0.7 to 1.1) and pain (mean difference 4.53 points; 95% CI 4.17 to 4.79) [62]. The results from the latter study are profoundly inconsistent with the other trials included in the systematic review [61]. Wolny and Linek have also published an open-label trial (n = 122) comparing neurodynamic techniques with no intervention (unblinded participants) showing essentially similar results as the sham-controlled trial [63].…”
Section: Do Neurodynamic Techniques Work?mentioning
confidence: 73%
See 1 more Smart Citation
“…However, study by Wolny and Linek (n = 180) found clinically important benefit for the neurodynamic group in the BCTQ symptom severity score (mean difference 1.22 points; 95% 1.1 to 1.4 points), BCTQ functional scale (mean difference 0.9; 0.7 to 1.1) and pain (mean difference 4.53 points; 95% CI 4.17 to 4.79) [62]. The results from the latter study are profoundly inconsistent with the other trials included in the systematic review [61]. Wolny and Linek have also published an open-label trial (n = 122) comparing neurodynamic techniques with no intervention (unblinded participants) showing essentially similar results as the sham-controlled trial [63].…”
Section: Do Neurodynamic Techniques Work?mentioning
confidence: 73%
“…A recent systematic review assessed the effect of neurodynamic techniques and found no clinically important benefit in pain or the BCTQ symptom severity score when they pooled data from trials with various control treatments [61]. Two sham-controlled trials were included in this review.…”
Section: Do Neurodynamic Techniques Work?mentioning
confidence: 99%
“…There is evidence about the positive effects of neurodynamic techniques on pain and functionality in peripheral entrapment neuropathies related to carpal tunnel syndrome [ 11 ], chronic low back pain [ 12 , 13 ], cervicobrachial pain syndrome [ 12 , 14 ], cubital tunnel syndrome [ 15 ], osteoarthritis pain of the hand [ 16 ], and plantar heel pain [ 12 ]. Although it is hypothesized that these techniques could have positive impacts on entrapment neuropathy symptoms by improving intraneural blood flow, axoplasmic flow, and neural connective tissue viscoelasticity and reducing intraneural edema and mechanosensitivity [ 9 ], they have not been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of this syndrome in US population is 3.72% and its incidence is 139.4 females out of 100 000 and 67.2 males out of 100 000 11 . There are many causes for this syndrome such as metabolic diseases, tendinitis, tendinosis, repetitive wrist activities, gripping activities ,constant pressure over median nerve, fracture of carpal bones, poor posture, lesions of median nerve , any trauma, arthritic changes and pregnancy but many have idiopathic cause 12,13,14 . The most common characteristics is tenderness and pain especially at night 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinesio taping can also be used for same purpose.When conservative treatment fails surgery is recommended in severe cases but there can be surgery related complications and failure 25 . Nonsurgical treatment also includes NSAIDs and Steroids 12,26,27 .…”
Section: Introductionmentioning
confidence: 99%